Short birth interval and its associated factors among multiparous women in Mieso agro-pastoralist district, Eastern Ethiopia: A community-based cross-sectional study - Wakeyo, Musa Mohammed; Kebira, Jemal Yusuf; Assefa, Nega; Dheresa, Merga (Frontiers in Global Women's Health, 2022)
Background: Recently, the concern with birth interval has acquired importance in public health and family planning because of its implication in fertility, maternal, and child health. Short birth interval is associated with adverse perinatal, maternal, and infant outcomes. Moreover, too short birth intervals lead to high fertility, which in turn contributed to accelerated population growth and undermines development efforts. This study aimed to investigate the prevalence of short birth interval and its associated factors among multiparous women in Mieso agro-pastoralist district, Oromia region, Eastern Ethiopia. Methods: A Community-based Cross-sectional study design was conducted from 1st to 30th March 2020. The multistage sampling technique was used to select 490 multiparous women. Data were collected by face-to-face interviewer-administered structured questionnaires. Bivariate and multivariable logistic regression analyses were executed. Model fitness and multicollinearity were checked. Statistically significant associations of outcome and independent variables were declared at a P-value < 0.05. Results: The prevalence of short birth interval was 56% (95% CI: 51.4-60.5) in the study area. Being married under 18 years (AOR=3.78, 95% CI:1.97-7.25), having formal education (AOR=0.23, 95% CI:0.11-0.47), having a husband with formal education (AOR=0.46, 95% CI:0.22-0.99), having awareness about optimum birth interval (AOR=0.47, 95% CI:0.24-0.91), having female index child (AOR=1.78, 95% CI:1.07-3.84), death of the index child (AOR=0.34, 95% CI:0.12-0.92), breastfeeding of the index child <24months (AOR=2.6, 95% CI:1.53-4.41), use of modern contraceptive (AOR=2.09, 95% CI:1.12-3.89), and decision making by a husband alone when to have a child (AOR=3.86, 95% CI:2.06-7.21) were significantly associated with short birth interval at a P-value less than 0.05. Conclusion: The overall prevalence of short birth interval among the study participants was high, as more than half of women had practiced short birth interval, indicating, still the majority of the mother and children in the study area are at high risk of mortality and morbidity associated with short birth interval. Thus, the current findings suggests that interventions that involve the provision of contraceptives and information on its benefit at points need to be adopted to reach the national and global target of maternal and child mortality reduction attributed to short birth interval.